Ryba - mifologičeskij proobraz lodki The Fish as a Mythological Prototype of the Boat - Dainius Razauskas (Studia Mythologica Slavica, 2011)
The known mythological ideas of the water body either as the way to the other world or as the very other world are first recalled in the article. Then, the ideas of the deceased sailing to the other world in boats or ships. After that, the archaic image of death as a big fish swallowing the deceased. This image, as a form of hut, is also traced in primitive initiations. Finally, it is furthermore maintained, on the grounds of some additional data, that the fish in this aspect is the mythological prototype of the boat or ship as such, which was firstly invented according to the knowledge gained during the corresponding initiation.